Mapping dengue risk hotspots based on sociological, environmental and climatic factors using geographical information system - Adnan, Ruhil Amal (2022)
Dengue fever (DF) and dengue haemorrhagic fever (DHF) continue to be major public health problems in Malaysia. These vector-borne diseases are transmitted by Aedes aegypti (Ae. aegypti) and Aedes albopictus (Ae. albopictus). Until today, there is no vaccine to control the outbreaks of DF and DHF. The better understanding of relationship between vectors, risk factors and infected human is crucial in devising strategy to control dengue.The main objective of this study is to develop dengue risk map based on sociological, environmental and climatic factors at hotspot areas for dengue transmission by using Geographical Information System (GIS). This research was carried out at three different localities; residential areas, routine areas and intersect areas. The mapping of transmission areas was produced based on interview with three hundred and seventy-nine respondents with dengue history from Parliament Batu and Parliament Wangsa Maju. The ovitrap survey was conducted as indicator for Aedes mosquito detection. The impact of sociological and environmental factors contributing to dengue cases were evaluated in this study by chi-square and binary regression. Pearson’s Correlation and Mann-Kendall Trend analysis were used for climate evaluation. Inverse Distance Weighting (IDW) was used for produce the map of each factor followed by Weightage analysis for risk maps. Finally, the validation of risk map was carried out by using kernel density estimation in order to identify the contributing factors in hotspot areas. Descriptive data indicated 118 (31%) respondents stayed at home, and 261 (69%) respondents went to work, school and college. The spatial distribution of dengue cases based on the residential areas showed the highest numbers of respondent from Parliament Batu were Kampung Padang Balang, Taman Dato’ Senu and Flat Sri Perak, while in Parliament Wangsa Maju were Kem Wardieburn and Seksyen 2. Light Rail Transit (LRT) Station of Wangsa Maju showed the highest numbers were visited by the respondent, and followed by Tar College. The most frequent intersect point presented at the map were nearby to Flat Sri Perak and Kem Wardieburn. Ae. albopictus was found to be most dominant species in study areas with Ovitrap Index values between 65% to 74%. The chi-square results showed there is a significant association between respondents who had one experience with dengue and lived in houses shaded with vegetation (95% CI = 0.263 and 0.836, p = 0.012) with playground area near the house (95%CI = 0.304 and 0.859, p = 0.011). Furthermore, a significant association with respondent who had once experienced by dengue was not present of playground at routine area (95%CI = 0.186 and 0.99, p = 0.036). The analysis from year 2012 to 2016 by using Pearson’s Correlation showed that dengue cases in Kuala Lumpur were significantly correlated with temperature, relative humidity and rainfall (p < 0.05). Mann-Kendall trend analysis showed in both 2012 and 2014 indicated the rising in dengue cases were affected by the increases in temperature and wind speed, while the relative humidty and rainfall affects the dengue with decreasing pattern. The risk map in residential setting showed high risk areas namely Flat Sri Perak mostly concentrated in Parlimen Batu, and Taman Setapak Indah in Parlimen Wangsa Maju. Routine area’s map showed high risk areas namely Sekolah Menengah Setapak Indah, Sekolah Menengah Bandar Baru Sentul and Sekolah Kebangsaan Danau Kota which mostly visited in study areas. The most concentrated intersect areas from risk map were located near to Kem Wardieburn, Sri Pelangi Condominium and Flat Sri Perak.The results indicated most factors in high risk and low risk areas from residential areas showed similarity between risk map and validation map excepting employment status, presence of construction areas, rainfall and wind speed. Routine areas showed four factors presented contradicting between risk map and validation which were presence of construction area, presence of playground area, rainfall and wind speed. Meanwhile, six factors presented contradicting in intersect areas were presence of construction area, presence of playground area, presence of vegetation, relative humidity, rainfall and wind speed. This study revealed that the most common areas for dengue-afflicted patients to be present in included the residential, work, and study areas. Dengue transmission can be influenced by a combination of multi factorial as they may collectively and indirectly contribute to the density of the Aedes mosquitoes. Risk map and validation from this study can be used by as a model for vector control program in order to predict the high risk areas and association factors in urban areas.